The potential role of nanomedicine in the treatment of breast cancer to overcome the obstacles of current therapies - Yang, Fan; He, Qingjie; Dai, Xiangpeng; Zhang, Xiaoling; Song, Dong (Frontiers in Pharmacology, 2023)
Breast cancer (BC) is the most frequently diagnosed malignant tumor among women in the world. BC is the heterogeneous tumor with different subtypes including luminal A-like, luminal B-like (HER2-/HER2+), HER2 enriched, and triple-negative BC. The therapeutic strategies including surgery, chemotherapy, radiotherapy, targeted therapy, and endocrine therapy are well developed and commonly used in the treatment of BC. However, some adverse effects of these conventional treatments limited their wide application in clinical. Therefore, it is necessary to develop more safe and more efficient individualized treatment strategies of the BC. Nanomedicine, as the most promising strategy for controlled and targeted drug delivery, is widely used in multiple aspects of cancer therapy. Importantly, accumulative evidences show that nanomedicine has achieved good outcomes in the treatment of BC and a huge amount of BC patients benefited from the nanomedicine related treatments. In this review, we summarized and discussed the major problems occurred during the administration of conventional treatment strategies for BC and the potential roles of nanomedicine in promoting the treatment efficacy of BC by overcoming obstacles of current treatment of BC.